Two years of newborn screening for cystic fibrosis in North Macedonia: First experience - Fustik S; Anastasovska V; Plaseska-Karanfilska D; Stamatova A; Spirevska L; Pesevska M; Terzikj M; Vujovic M (Balkan Journal of Medical Genetics, 2021)
There is a widely accepted consensus on the benefits of newborn screening (NBS) for cystic fibrosis (CF) in terms of reduced disease severity, improved quality of life, lower treatment burden, and reduced costs. More and more countries in the world are introducing NBS for CF as a national preventive health program. Newborn screening for CF was introduced in the Republic of North Macedonia (RNM) in April, 2019, after a pilot study of 6 months in 2018. A two-step immunoreactive trysinogen (IRT-IRT) algorithm is performed, and then a sweat test for confirmation/exclusion of the CF diagnosis when the IRT values were both over the cutoff (70.0 and 45.0 ng/mL, respectively). In cases with confirmed diagnosis of CF (a sweat chloride concentration >60.0 mmol/L) or with intermediate sweat test results (a sweat chloride concentration of between 30.0 and 59.0 mmol/L), CF transmembrane conductance regulator (CFTR) mutation analysis is performed. By the end of 2020, over a period of 27 months, including the pilot study period, a total number of 43,139 newborns were screened for CF. Seventeen (0.039%) newborns were diagnosed with CF. In all newly discovered CF cases by screening, the diagnosis was confirmed by determination of the CFTR mutations. The most common CFTR mutation, F508del, was found with an overall incidence of 70.6%. Other more frequent mutations were G542X (11.8%) and N1303K (5.9%). Four mutations were found in one CFTR allele each: G1349D, G126D, 457TAT>G and CFTRdupexon22, with the last one being newly discovered with unknown consequences. An incredibly large difference was found in the incidence of the disease between the Macedonian and Albanian neonatal population, with almost four time higher prevalence among Albanians (1:4530 vs. 1:1284).